Variability of elite maize (Zea mays L.) varieties at different row spacing in Guinea Savannah Region of Nigeria - Nyamve Simon Mnzughul; Demben Moses Esang; Angus Onwudiwe Ikeh (Research and Social Study Institute, 2023)
Varieties and spacing are among the factors determine crop yield. Field experiment was carried out at the North Core College of Agronomy Teaching and Research, Joseph Sarwuan Tarka University, Makurdi to determine the effects of intra row spacing on the performance of three maize varieties in Makurdi. The experimental design used was 3 x 4 factorial arrangement laid out in a Randomized Complete Block Design, replicated thrice. The treatments were three (3) maize varieties and four (4) different intra-row spacing (20 cm, 30 cm, 40 cm and 50 cm). Data were collected on growth, yield and yield component parameters were subjected to analysis of variance. Significant means were subjected to least significant difference (LSD). The result showed significant differences among the maize varieties, row spacing and treatment interactions which indicated the presence of genetic and environmental effects on maize performance. The superiority of Sammaz-51 over the other varieties was observed as it produced significant seed yield. Result showed increase in intra row spacing with increase in more number of leaves per plant which were significantly longer and wider while least was recorded in a closer spacing. Increase in plant spacing beyond 40 cm intra-row was found to reduce cob weight, weight of seeds per cob as well as 1000-seed weight. Based on the study findings, maize farmers were advised to adopt increase intra-row spacing up to 40 cm for optimum yield of maize in savannah region of Nigeria.